Trajetórias dançantes : influências constitutivas do ser professor de dança - Jesus , Caroline Kummer de (2015)
From the identification of important moments in the personal life story and professional about dance teachers as dancers, teachers and academics from dance course or physical education, this research presents the objective understand through reports of teachers how those moments influence their teaching constitution in view of its entirety. It brings in its theoretical framework relevant authors on subject: Catanante (2000), Dantas (1999), Freire (2013), Josso (2004), Marques (2010), Nóvoa (1992), Palmer (2012), Strazzacappa and Morandi (2012), Tardif (2002). Through methodological qualitative approach, was used as information collection instrument the semi interview structured that was performed individually with nine teachers belonging to two dance schools. The analysis and interpretation of information were made through by Discursive Textual Analysis proposed by Moraes and Galiazzi (2011). The results of this research pointed out as moments of the trajectory of the interviewed as dancers and teachers. Become more present influences in their speeches: the marks left by teachers who passed through the lives of the interviewees who have become references in make in their teaching, both in teaching and in established relationships, as well as "put themselves" in place of the students because they have gone through similar situations.Entry into the teaching took intrinsically related to their career in the dance, and the taste for teaching the subject narrated more strongly about that choice. The meaning of teaching is linked to the passion for this profession, as well as the "matter" taught: the dance. The academic backgrounds, although different, have become important in the lives of teachers, providing moments of reflections about the body, dance, their students and their own teaching, bringing singularities as the courses offered in each course. With the teaching practice, knowledge were built: by validating their knowledge by "trial and error", managing to deal with the unexpected; improvement of interpersonal relations as well as characteristics considered important for teaching; handling facilities and difficulties encountered in dance education. Over the reports, it became clear that, while the teacher of dance is constituted teacher, denounces its constitution as a person from the perspective of a whole (dimensions: social, emotional, spiritual and rational) identifying the I that Being who teaches dance.